Assessing the effects of targeted soccer exercises on the physical fitness of 15-16-year-old schoolchildren - Julia Popovych; Olena Nesen; Krzysztof Prusik; Vasyl Lutskyi (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Soccer activities are a good means of physical activity for high school students. However, the living conditions of teenagers in war zones necessitate organizing education in an online format. Overall, this affects the physical fitness of adolescents. The purpose of the study was to evaluate the impact of soccer exercises on the physical fitness indicators of high school students under the conditions of online learning.